Impact of climate change on women mental health in rural hinterland of Pakistan - Daraz, Umar; Khan, Younas; Alsawalqa, Rula Odeh; Alrawashdeh, Maissa N.; Alnajdawi, Ann Mousa (Frontiers in Psychiatry, 2024)
BackgroundClimate change significantly impacts global well-being, with rural and agricultural communities, particularly women, bearing a disproportionate burden. In Pakistan’s Malakand Division, women face increased mental health challenges due to environmental stressors such as temperature rise, extreme weather, and environmental degradation. These stressors are expected to exacerbate issues like stress, anxiety, and depression. Understanding their effects on rural women’s mental health is crucial for developing effective intervention strategies.MethodologyThis study employs quantitative methodologies to assess the impact of climate change on the mental health of rural women in Malakand Division, focusing on Dir Upper, Dir Lower, and Shangla districts. A cross-sectional design was used, with a sample size of 600 women selected through multistage cluster sampling for geographic representation. Data were collected using structured questionnaires addressing stress, anxiety, and community dynamics. Data were analyzed using multiple regression, structural equation modeling (SEM), ANOVA, and logistic regression.ResultsThe results revealed that climate change factors—temperature increase (β = 0.42, p < 0.01), extreme weather events (β = 0.36, p < 0.01), precipitation changes (β = 0.31, p < 0.05), and environmental degradation (β = 0.28, p < 0.05)—significantly impacted rural women’s mental health. High levels of stress (72%), anxiety (68%), and depression (56%) were reported. Social support (β = -0.45, p < 0.01), community cohesion (β = -0.37, p < 0.05), access to resources (β = -0.39, p < 0.01), and cultural norms (β = -0.33, p < 0.05) were key factors mitigating the effects of climate stress. Gender disparities were evident, with women showing higher mental health challenges compared to men in similar conditions.ConclusionThe study concludes that climate change significantly exacerbates mental health issues for rural women. It highlights the need for gender-sensitive, community-based interventions that address both climate adaptation and mental health. Strengthening community resilience, improving access to resources, and investing in healthcare and education are vital for enhancing well-being in the face of climate change.